Effect of antepartum vitamin D3 (cholecalciferol) and postpartum oral calcium administration on serum total calcium concentration in Holstein cows fed an acidogenic diet in late gestation. (May 2021) - Hajikolaei, Mohammad Rahim Haji; Nouri, Mohammad; Amirabadi, Soroush Hassanpour; Shariari, Ali; Constable, Peter D.
Abstract: Several strategies are available to control periparturient hypocalcaemia in dairy cows. Three complementary strategies were applied in this study: feeding a low DCAD (acidogenic) ration during late gestation, oral vitamin D3 (cholecalciferol) administration in late gestation, and oral Ca administration immediately after parturition. Multiparous Holstein cows ( n  = 240) were fed an acidogenic ration in late gestation and randomly assigned to one of three treatment groups. Group A ( n  = 80) were fed the acidogenic diet without supplementary Ca or cholecalciferol. Group Ca + A ( n  = 80) received 50 g of Ca as an oral bolus at calving and 12 h later. Group D3  + Ca + A (n = 80) were administered 3 mg of cholecalciferol orally each day starting 3 to 5 days before the anticipated calving date and 50 g of Ca as an oral bolus at calving and 12 h later. Blood and urine samples were obtained periodically from a random subset of 20 cows in each group from day 5 antepartum to day 21 postpartum and selected analytes measured. Data was analyzed using mixed models analysis. Serum Ca concentrations in group D3  + Ca + A were higher 12 h before and at parturition, compared to the two other groups. Oral Ca administration transiently increased mean serum Ca concentrations at 6 h after treatment initiation in groups D3  + Ca + A and Ca + A. We conclude that daily oral administration of 3 mg of cholecalciferol for up to 5 days before calving, combined with feeding an acidogenic ration in late gestation and oral Ca immediately after parturition, provided the highest periparturient serum Ca concentrations. Highlights: In the current study the combining three strategies for controlling periparturient hypocalcemia in 240 dairy cows were hypothesized Feeding an acidogenic (low DCAD) ration in late gestation Oral administration of 25-hydroxyvitamin D3 (calcidiol) in late gestation Oral administration of calcium immediately after parturition Daily oral administration 25-hydroxyvitamin D3 in late gestation, with oral CaCl2 immediately after parturition provided greater periparturient serum total Ca concentrations